Live video streaming for mobile devices: an application on android platform - Mantoro, Teddy; Ayu, Media Anugerah; Jatikusumo , D (2012)
Television or TV, including internet TV, is a very attractive service to the public and at the same time mobile devices such as tablet or smartphone with broadband network, as a handy device, is available anywhere and anytime. Unfortunately many TV stations have live streaming services which can only be enjoyed on the website but has a poor quality for mobile devices. This paper proposes a framework to allow mobile devices to receive a live streaming service using client server approach. The mobile devices, as a client, will connect to the server and receive a digital broadcasts including decode and display the schedule of events in real time mode, as proof of concept, in the Android platform. This paper shows that users can access live streaming and display images in a good quality through their mobile. Moreover, users are capable to select the required date to get real time schedule of TV events on Android smartphone.